A Carbonyl Compound‐Based Flexible Cathode with Superior Rate Performance and Cyclic Stability for Flexible Lithium‐Ion Batteries. Issue 4 (11th December 2017) - Amin, Kamran; Meng, Qinghai; Ahmad, Aziz; Cheng, Meng; Zhang, Miao; Mao, Lijuan; Lu, Kun; Wei, Zhixiang
Abstract: A sulfur‐linked carbonyl‐based poly(2, 5‐dihydroxyl‐1, 4‐benzoquinonyl sulfide) (PDHBQS) compound is synthesized and used as cathode material for lithium‐ion batteries (LIBs). Flexible binder‐free composite cathode with single‐wall carbon nanotubes (PDHBQS–SWCNTs) is then fabricated through vacuum filtration method with SWCNTs. Electrochemical measurements show that PDHBQS–SWCNTs cathode can deliver a discharge capacity of 182 mA h g −1 (0.9 mA h cm −2 ) at a current rate of 50 mA g −1 and a potential window of 1.5 V–3.5 V. The cathode delivers a capacity of 75 mA h g −1 (0.47 mA h cm −2 ) at 5000 mA g −1, which confirms its good rate performance at high current density. PDHBQS–SWCNTs flexible cathode retains 89% of its initial capacity at 250 mA g −1 after 500 charge–discharge cycles. Furthermore, large‐area (28 cm 2 ) flexible batteries based on PDHBQS–SWCNTs cathode and lithium foils anode are also assembled. The flexible battery shows good electrochemical activities with continuous bending, which retains 88% of its initial discharge capacity after 2000 bending cycles. The significant capacity, high rate performance, superior cyclic performance, and good flexibility make this material a promising candidate for a future application of flexible LIBs. Abstract : A carbonyl compound (oligomeric poly(2, 5‐dihydroxyl‐1, 4‐benzoquinonyl sulfide)‐based flexible cathode with superior rate performance and cyclic stability is reported. The carbonyl compound is served as active material, and single‐wall carbon nanotube, can act as a current collector and binder. Since all the materials used are inherently flexible, this flexible electrode is ready for a potential application in flexible lithium‐ion batteries.